(3bUGFO aj eOM GdfHj Ydjg GdUdGI hGdSdGes - (3LGfj RGOI YHO Gddg Hf eUWais ((3YHO Gddg Hf eUWai LGHj RGOIs)
(3ChdgG (B:s
(3HSe Gddg (B... (3hdG CQbJ dPcQ GdHGf hGdYde (B** (3acja JfcQ MHG HYOeG TgOJ (B** (3Hg Ydjc YOhd GdOeY hGdSbe (B..s
(3BNQgG (B:s
.. (3Ndb YXje eKd Ndb eMeO (B, (3RGA , Rjf RjGQI bHQg caGQI , ddRGFQjf aRQ VQjM eMeO (B... (3jGA jejf dG CMd Yf YgOg(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B9(1) / 1595s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJUha hGdBOGH GdTQYjIs